Wewenang Auditor Badan Pengawasan Keuangan dan Pembangunan (BPKP) Mengungkap Kerugian Negara dalam Tindak Pidana Korupsi - Iryana Anwar (Kyadiren, 2019)
This study aims to determine the authority relationship between Finance and Development Supervisory Agency (BPKP) Auditor and the South Sulawesi Police Institution, the legal status of the BPKP auditor's inspection and evidence in criminal procedural law, and obstacles in the BPKP auditor's inspection. This study employed an empirical juridical approach to identify how a rule actually applies in society. The data were obtained through field observations, interviews with investigators from South Sulawesi Police Institution and BPKP Auditor, and the study of various related documents. The results showed that the authority between The Regional Police and the BPKP Auditor was only dependent on a request for assistance to carry out financial and state economic calculations based on a cooperation agreement or Memorandum of Understanding (MOU) between the National Police Institution and BPKP. Therefore, the BPKP indeed plays a role in revealing corruption indications despite its authority only for calculating state losses, where if the BPKP’s audit report states a loss, the Regional Police Investigator increases the stage of the Investigation, but if the results state no loss, the investigation will be stopped. Thus, there is no indication of corruption.